Chapter 15 Decolonisation in Learning Development - Koromila, Georgia (Taylor & Francis, 2024)
Over the last decade, efforts to 'decolonise' Higher Education have gained ground in universities across the world. As Learning Developers, we must keep abreast of subsequent changes to curricula and pedagogy, so that we can help students develop the skills they need to succeed in a decolonised university. We should also consider how we can contribute to this discussion by questioning and re-evaluating our own practices through a decolonial lens. This chapter offers a departure point for exploring these questions, by reflecting on opportunities, barriers, and some early successes, all the while recognising that well-defined answers, for now, may remain elusive.